Analysis of the relationship between heart rate variability and maximal oxygen uptake in rower male - Li, Z.; Gao, B.; Ruan, E. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of this study was to investigate the relationship between HRV and maximal oxygen uptake in male rowers. Summary: 1) It has been shown that male rower athletes should have a better aerobic capacity, the higher the HRV grows. 2) Significant positive correlation (P<0.01) both VO2max and total variability (TV.rri) indicate autonomic nervous system accommodate is important in determining performance in endurance exercise of rower athlete. 3) Characteristics of HRV in rower athlete can be a contributor to their long training, maybe, this regular long training stimulus is required in order for to occur higher the VO2max.